Cardiovascular Safety Pharmacology of Sibutramine - Yun, Jaesuk (Biomol Ther (Seoul), 2015)
Sibutramine is an anorectic that has been banned since 2010 due to cardiovascular safety issues. However, counterfeit drugs or slimming products that include sibutramine are still available in the market. It has been reported that illegal sibutramine-contained pharmaceutical products induce cardiovascular crisis. However, the mechanism underlying sibutramine-induced cardiovascular adverse effect has not been fully evaluated yet. In this study, we performed cardiovascular safety pharmacology studies of sibutramine systemically using by hERG channel inhibition, action potential duration, and telemetry assays. Sibutramine inhibited hERG channel current of HEK293 cells with an IC(50) of 3.92 μM in patch clamp assay and increased the heart rate and blood pressure (76 Δbpm in heart rate and 51 ΔmmHg in blood pressure) in beagle dogs at a dose of 30 mg/kg (per oral), while it shortened action potential duration (at 10 μM and 30 μM, resulted in 15% and 29% decreases in APD(50), and 9% and 17% decreases in APD(90), respectively) in the Purkinje fibers of rabbits and had no effects on the QTc interval in beagle dogs. These results suggest that sibutramine has a considerable adverse effect on the cardiovascular system and may contribute to accurate drug safety regulation.